Pengaruh Luas Wilayah, Populasi Penduduk, Rasio Efisiensi Terhadap Financial Distress di Pemerintah Provinsi Jawa Tengah Periode 2020 - 2024 - Rizqi Darma Saputra; Banu Witono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of regional area size, population, and efficiency ratio on financial distress in local governments of Central Java Province during the 2020–2024 period. Financial distress in the public sector reflects the inability of local governments to manage public finances sustainably, which may reduce the quality of public services. This research employs a quantitative approach using a causal method. The research sample consists of 35 local governments, including 29 regencies and 6 municipalities in Central Java Province. Binary logistic regression is applied to examine the influence of independent variables on financial distress. The results indicate that regional area size has a significant effect on financial distress, population has a significant effect on financial distress, and the efficiency ratio has a significant effect on financial distress. These findings suggest that geographic characteristics, demographic conditions, and financial management efficiency are crucial determinants of local government financial conditions. This study is expected to provide insights for local governments in formulating more effective and sustainable financial management policies to reduce the risk of financial distress.